If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(6x + -5)(4x + 5) = 0 Reorder the terms: 2(-5 + 6x)(4x + 5) = 0 Reorder the terms: 2(-5 + 6x)(5 + 4x) = 0 Multiply (-5 + 6x) * (5 + 4x) 2(-5(5 + 4x) + 6x * (5 + 4x)) = 0 2((5 * -5 + 4x * -5) + 6x * (5 + 4x)) = 0 2((-25 + -20x) + 6x * (5 + 4x)) = 0 2(-25 + -20x + (5 * 6x + 4x * 6x)) = 0 2(-25 + -20x + (30x + 24x2)) = 0 Combine like terms: -20x + 30x = 10x 2(-25 + 10x + 24x2) = 0 (-25 * 2 + 10x * 2 + 24x2 * 2) = 0 (-50 + 20x + 48x2) = 0 Solving -50 + 20x + 48x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-25 + 10x + 24x2) = 0 Factor a trinomial. 2((-5 + -4x)(5 + -6x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-5 + -4x)' equal to zero and attempt to solve: Simplifying -5 + -4x = 0 Solving -5 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -4x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -4x = 0 + 5 -4x = 0 + 5 Combine like terms: 0 + 5 = 5 -4x = 5 Divide each side by '-4'. x = -1.25 Simplifying x = -1.25Subproblem 2
Set the factor '(5 + -6x)' equal to zero and attempt to solve: Simplifying 5 + -6x = 0 Solving 5 + -6x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -6x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -6x = 0 + -5 -6x = 0 + -5 Combine like terms: 0 + -5 = -5 -6x = -5 Divide each side by '-6'. x = 0.8333333333 Simplifying x = 0.8333333333Solution
x = {-1.25, 0.8333333333}
| -5-5=0 | | 3+log^4(2x+6)=6 | | -16=-2(3+x) | | (-4i)(6i)=0 | | x+2=-2x+14 | | 4(2n-3)=(5n+4)+3 | | [2x+5]=14 | | 20=-36x-4(-6-2) | | 4-(7y-5)=6y-4 | | -16x^2+50x+15=0 | | (ax+by)(cx+y)=x | | 20x+5=21x-5 | | 20x=21x | | 80=(10+30p)-(150+20p) | | 10a+7=6a+10+3a | | 6(2x-7)+4=12x-38 | | -8u+30=2u | | x+3=-4x+23 | | 16x^2+50x+15=0 | | 18-(1/22)(2x)=9-(1/22)(x) | | (4x+5)(5x-1)=0 | | 2x+0.5x=770 | | log^2(x-1)=4 | | (2/3)(x+4)=(3/8)(x-3) | | 3x-8=4x-25 | | 6.1w+2.2=0.5w-3.4 | | 950+800+3x=800+300+8x | | (4n+18)+(5n+27)=180 | | 3200=8x+4x^2 | | .50x+.05(130)=.25(66) | | 0.36x+026=3.86 | | 6x=13-3y |